Strategi manajemen risiko pada Bank Syariah beserta tantanganya - Asqolani, Ahmad Maulana Kholil Muhajir Madani (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze risk management strategies in Islamic banks and identify challenges faced in their implementation. The approach used is descriptive-qualitative, using a literature review method from five primary sources: Abbas et al. (2020), Boegiyati et al. (2024), Fasa (2013), Nelly et al. (2022), and Styawati (2024), supplemented by recent references from various relevant journals. The study results indicate that Islamic banks face various key risks, including financing, liquidity, operational, legal, sharia compliance, reputational, and technological risks. The unique characteristics of Islamic banking, based on the profit-sharing principle, differentiate its risk profile from that of conventional banks. Therefore, a comprehensive risk management strategy must be implemented through the stages of risk identification, measurement, monitoring, and control in accordance with sharia principles. The implementation of a risk management system in Islamic banks requires the integration of prudential banking principles and Islamic principles of justice, including oversight by the Sharia Supervisory Board, the use of information technology, and human resource capacity building. Key challenges include the complexity of contracts, inadequate regulations, low public financial literacy, and cyber risks resulting from banking digitalization. Addressing these challenges requires innovative technology-based risk control systems, improved employee competency, and regulatory policies aligned with Sharia principles.